2006
DOI: 10.1002/cm.20166
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to study fibroblast migration

Abstract: This paper presents a new approach to study cell migration. Human tendon fibroblasts were plated on silicone membranes coated with 10 lg/ml ProNectin-F. The silicone surfaces were micro-fabricated with parallel microgrooves, with 10 lm ridge and groove width, and 3 lm groove depth. Fibroblasts grown in the microgrooves had an elongated shape and oriented along the microgroove direction. They also moved along the same direction instead of \random walk" when cells migrate on smooth culture surfaces. In response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
(15 reference statements)
2
21
1
Order By: Relevance
“…As reported [15], the membrane surfaces were micro-fabricated to create parallel microgrooves with 10 mm ridge and groove width and 3 mm groove depth. Meanwhile, smooth silicone membranes were used as a control and both types of membranes were coated with 10 ng/ml fibronectin (Roche, Indianapolis, IN) to promote cell attachment.…”
Section: Microgroove Membrane As a Cell Culture Substratementioning
confidence: 99%
See 1 more Smart Citation
“…As reported [15], the membrane surfaces were micro-fabricated to create parallel microgrooves with 10 mm ridge and groove width and 3 mm groove depth. Meanwhile, smooth silicone membranes were used as a control and both types of membranes were coated with 10 ng/ml fibronectin (Roche, Indianapolis, IN) to promote cell attachment.…”
Section: Microgroove Membrane As a Cell Culture Substratementioning
confidence: 99%
“…To enforce an elongated morphology of cultured tenocytes, previously reported microgroove silicone membrane, a gift kindly provided by Dr. James Wang from University of Pittsburgh [15], was employed for the study. As reported [15], the membrane surfaces were micro-fabricated to create parallel microgrooves with 10 mm ridge and groove width and 3 mm groove depth.…”
Section: Microgroove Membrane As a Cell Culture Substratementioning
confidence: 99%
“…fibroblast cells with smooth muscle properties [4]. Some studies have suggested that myofibroblasts have reduced motility relative to less differentiated fibroblasts [6,7]. Using a microgrooved surface migration assay that monitors cell migration in one dimension, Thampatty and Wang [6] found that once human fibroblasts differentiated into myofibroblasts they were less motile than the undifferentiated controls.…”
Section: Evaluation Of This Hypothesismentioning
confidence: 99%
“…Some studies have suggested that myofibroblasts have reduced motility relative to less differentiated fibroblasts [6,7]. Using a microgrooved surface migration assay that monitors cell migration in one dimension, Thampatty and Wang [6] found that once human fibroblasts differentiated into myofibroblasts they were less motile than the undifferentiated controls. This reduction in migration may be associated with the incorporation of α-smooth muscle actin in stress fibres, a widely accepted marker of myofibroblast formation, and the development of supermature focal adhesions which exerts greater stress compared to other focal adhesions [8,9].…”
Section: Evaluation Of This Hypothesismentioning
confidence: 99%
“…Cell migration is another essential process that ensures not only tissue development and maintenance of homeostasis but also provides a successful wound healing process [31]. The in vitro scratch assay is a suitable model for the preliminary studies, providing the possibility to investigate the influence of separate extracellular matrix components on the cell migration properties [9].…”
Section: Discussionmentioning
confidence: 99%